Silicon Valley where the future was born - Maclowry, Randall; Murphy, Michael 1938-; Else, Jon 1944- (PBS Distribution, 2013)
The birth of Silicon Valley -- Shockley Semiconductor -- The traitorous eight -- The space race -- Mass producing a reliable product -- The integrated circuit -- Fairchild increase competition -- Fairchildren splinters -- Intel and the microprocessor
Dokumentarfilm. USA. 2013
Keywords: Geschichte; Personal Computer; Silicon Valley; Noyce, Robert N. 1927-1990 / Noyce, Robert N. 1927-1990; Fairchild (Firm) / History / Fairchild (Firm); Microelectronics industry / History / California / Santa Clara Valley (Santa Clara County); Computer industry / History / California / Santa Clara Valley (Santa Clara County); High technology industries / History / California / Santa Clara Valley (Santa Clara County); Computer industry; High technology industries; Microelectronics industry / California / Santa Clara Valley (Santa Clara County); Television programs / United States / History / Historical television programs / Documentary television programs / Nonfiction television programs / Video recordings for the hearing impaired; Film; DVD-Video